2013
DOI: 10.1007/s10461-013-0445-9
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Antiretroviral Therapy and Clinical Outcomes Among Young Adults Reporting High-Risk Sexual Behavior, Including Men Who Have Sex with Men, in Coastal Kenya

Abstract: African men who have sex with men (MSM) face significant stigma and barriers to care. We investigated antiretroviral therapy (ART) adherence among high-risk adults, including MSM, participating in a clinic-based cohort. Survival analysis was used to compare attrition across patient groups. Differences in adherence, weight gain, and CD4 counts after ART initiation were assessed. Among 250 HIV-1-seropositive adults, including 108 MSM, 15 heterosexual men, and 127 women, patient group was not associated with attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 32 publications
3
53
2
1
Order By: Relevance
“…The HIV prevalence in this survey was lower than what has been reported in most African settings. 3,6,9 This could be due to the fact that the most of our participants were young (mean age of 23.2 years). However, the significant association between HIV prevalence and age reflects the cumulative effect of long-term risk behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HIV prevalence in this survey was lower than what has been reported in most African settings. 3,6,9 This could be due to the fact that the most of our participants were young (mean age of 23.2 years). However, the significant association between HIV prevalence and age reflects the cumulative effect of long-term risk behavior.…”
Section: Discussionmentioning
confidence: 99%
“…3Y5 Studies have pointed out that the high burden of HIV in sub-Saharan Africa occurs among populations reporting high-risk sexual behavior such as transactional sex and anal intercourse. 6 Men who have sex with men suffer significant stigma and discrimination 3,6 ; hence, they are reluctant to access health services. Because of a lack of social acceptance, MSM may end up with self-stigma, which leads to depression, alcohol, and substance abuse and, in turn, risky sexual practices.…”
Section: Conclusion: Hiv Prevalence Of Msm Was Lower Than What Has Beenmentioning
confidence: 99%
“…MSM were recruited for these cohort studies if they reported multiple sex partners, anal intercourse, sex work or an STI in the past 3 months. MSM who were HIV-1 negative at screening were enrolled in an open HIV-1 vaccine feasibility cohort5; MSM who were HIV-1 positive at screening were enrolled in a parallel cohort to receive HIV-1 care at the same research clinic 8. Enrolled men received quarterly risk-reduction counselling and HIV-1 testing (if previously seronegative), and had a medical history and physical examination at each scheduled visit.…”
Section: Methodsmentioning
confidence: 99%
“…21, 27 Further, stigma and discrimination could also increase barriers to testing HIV 2831 and adherence to ART. 32 …”
Section: Men Who Have Sex With Men (Msm)mentioning
confidence: 99%